2019
DOI: 10.1111/jeb.13573
|View full text |Cite
|
Sign up to set email alerts
|

No evidence that Y‐chromosome differentiation affects male fitness in a Swiss population of common frogs

Abstract: The canonical model of sex‐chromosome evolution assigns a key role to sexually antagonistic (SA) genes on the arrest of recombination and ensuing degeneration of Y chromosomes. This assumption cannot be tested in organisms with highly differentiated sex chromosomes, such as mammals or birds, owing to the lack of polymorphism. Fixation of SA alleles, furthermore, might be the consequence rather than the cause of recombination arrest. Here we focus on a population of common frogs (Rana temporaria) where XY males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…10 ‐6 to 10 –3 probability). Sex‐reversed individuals were found to be fertile in some ectothermic vertebrates (Devlin & Nagahama, 2002; Edmunds, McCarthy, & Ramsdell, 2000; Holleley et al., 2015), and in common frogs, XX males appear to be fertile and as successful in mating as XY males (Alho et al., 2010; Veltsos et al., 2019). If sex‐reversed individuals do reproduce in nature, the biased sex ratios of their progeny may lead to changes in the population sex ratio, sex chromosome frequencies and ultimately the sex‐determination system (Bókony et al., 2017; Quinn, Sarre, Ezaz, Marshall Graves, & a, & Georges, A., 2011; Wedekind, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…10 ‐6 to 10 –3 probability). Sex‐reversed individuals were found to be fertile in some ectothermic vertebrates (Devlin & Nagahama, 2002; Edmunds, McCarthy, & Ramsdell, 2000; Holleley et al., 2015), and in common frogs, XX males appear to be fertile and as successful in mating as XY males (Alho et al., 2010; Veltsos et al., 2019). If sex‐reversed individuals do reproduce in nature, the biased sex ratios of their progeny may lead to changes in the population sex ratio, sex chromosome frequencies and ultimately the sex‐determination system (Bókony et al., 2017; Quinn, Sarre, Ezaz, Marshall Graves, & a, & Georges, A., 2011; Wedekind, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Here we found that the ZW/ZZ system may maintain healthier sex ratios for longer, and persist more than two times longer, than the XX/XY system if the sex-reversed males can reproduce like normal males and produce viable, fertile WW offspring that are resistant to masculinization. These conditions stand in various taxa [ 10 , 17 , 33 , 41 43 , 56 ], although our empirical knowledge on WW or masculinized individuals in nature is scarce. Moreover, most ectothermic vertebrates possess homomorphic sex chromosomes that show no signs of degeneration, suggesting that sex-reversed and WW individuals should be viable and fertile in the majority of these taxa [ 4 , 44 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…0.0002 probability). Sex-reversed individuals were found to be fertile in some ectothermic vertebrates (Devlin & Nagahama, 2002;Edmunds, McCarthy, & Ramsdell, 2000;Holleley et al, 2015), and in common frogs XX males appear to be fertile and as successful in mating as XY males (Alho et al, 2010;Veltsos et al, 2019). If sex-reversed individuals do reproduce in nature, the biased sex ratios of their progeny may lead to changes in the population sex ratio, sex-chromosome frequencies, and ultimately the sex-determination system (Bókony et al, 2017;Quinn et al, 2011;Wedekind, 2017).…”
Section: Discussionmentioning
confidence: 99%